Neurobiological underpinnings of bipolar disorder focusing on findings of diffusion tensor imaging: a systematic review - Duarte,Juliana A. (2016)
Objective: To review the available data on diffusion tensor imaging (DTI) of subjects with bipolar disorder (BD), with a particular focus on fractional anisotropy (FA) in white matter (WM) tracts. Methods: The PubMed/MEDLINE database was searched for relevant articles, which were included in a systematic review of the literature. FA reductions and WM abnormalities were divided anatomically into three groups: commissural tracts, association tracts, and projection tracts. Results: Eighteen studies met the inclusion criteria. The corpus callosum was the main impaired commissural tract as demonstrated by FA reductions. Five studies reported FA reductions in the cingulum. Two studies reported decreased FA in the anterior thalamic radiation, and one in the corticospinal tract. Conversely, three studies found increased FA values in WM tracts involved in BD pathophysiology. Conclusion: Despite considerable heterogeneity, these results indicate a direct link between executive cognitive functioning and abnormal WM microstructural integrity of fronto-limbic tracts in patients with remitted BD, providing further evidence of the neuronal disruption that underlies BD symptomatology.